LIFE CYCLE ASSESSMENT STUDY FOR MANAGING ELECTRONIC WASTE USING LANDFILL TECHNOLOGY - Nurul Aini, Osman; Norazli, Othman; Roslina, Mohammad; Shreeshivadasan, Chelliapan (2018)
Electronic waste has become a serious environmental issue due to its rapid growth in volume and its hazardous content. As a new addition to the waste stream, the emergence and rapid increase of electronic waste demands an inclusive management system. The management of electronic waste using landfill technology will pose significant amount of problem for environment and human health. Toxic substances from electronic waste dumping at the landfill site may be found in various type of emission such as leachate and landfill gas from landfill site. This study aims to evaluate the environmental impact produced by management of the electronic waste using landfill technology. In this study, a life cycle assessment technique will be used to evaluate the impact of the management of electronic waste using landfill technology. The methodologies of this study are field study, data collection, model development of landfill system, computer calculation development and impact analysis study. The inputs of the system are management of 700 tonnes/day of electronic waste, which were generate from residential, commercial and industrial premises. The fuel usage for transportation activities are 1,069.44 liters per day. The energy usage for processing activities at secured Landfill site are 2,800 liters per day for diesel usage and 2.33 MW/day for electricity usage The results of this study shows that there is no recovery material produced from the landfill. The emissions produced from the processing activity in the landfill system are 583.1 tonnes/day of leachate as well as 2,249,100 m3/day landfill gas. The landfill system produces 59.19 kg water pollutant and 866.9 kg air pollutant. The finding of the study shows that, landfill technology unable to recover world raw materials such as plastics, metals, glass and others. In addition, the emissions such as water and air emission also generated from the system. To minimize the impact of Landfill Technology for managing electronic waste, pollution control facilities such as air pollution control and water pollution control is essential to eliminate the pollutant from released to the atmosphere and water bodies.